Optimalisasi Proses Stock Opname Alat Tulis Kantor (ATK) Melalui Digitalisasi Quick Response Code (Qr Code) Pada PT Surabaya Industrial Estate Rungkut (SIER) - Nirawati, Lia; Seibinna, Tiara Meyla (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The stock taking process is an important activity in inventory management which aims to ensure conformity between inventory records and the physical number of goods on hand. PT Surabaya Industrial Estate Rungkut (SIER) is facing challenges in the stock taking process for Office Stationery (ATK) which has been done manually. This manual process is time consuming, prone to recording errors, and less efficient. Therefore, this research aims to optimize the ATK stock taking process through digitization using QR Codes. By implementing the QR Code system, each ATK item will be given a QR Code label containing detailed information about the item. Officers can scan the QR Code using a mobile device to record it automatically. This method is expected to increase data accuracy, speed up the stock taking process, and reduce human error. The research results show that the use of QR Codes in the ATK stock taking process at PT SIER is able to increase time efficiency by up to 50%, reduce recording errors by up to 70%, and increase officer satisfaction with an easier and faster process. It is hoped that digitalization through QR Codes can be adopted by other companies to optimize their inventory management.